How nurse express their caring behavior to patients with special needs (Research Report) - Elly Nurachmah (Fakultas Ilmu Keperawatan Universitas Indonesia, 2001)
The purpose of the research was to explore how nurses who work in the specific nursing care facilities express their caring behavior to patients with special needs. A descriptive explorative research design was conducted, and a thirty item questions was administered to nurses who work in ICU, CCU, Casualty/Emergency, Stroke unit, and hemodialysis units in hospitals in Jakarta Metropolitan. The questions were derived from ten carrative factors of Watson’s theory of Caring (Watson, 1994). One hundred sixty five questions was distributed during a month of data collection period, and only 102 questionnaires fulfilled the criteria. Among the findings showed that more than 75% of respondents appreciated clients as persons who have privascy and dignity. The recommendations were directed to nursing authority in the area of education that caring spirit should be grown since the early years of nursing education. In addition, the nursing managers should pay more attention to create conducive environment for nurses to build more cohesive – trust relationship with clients and families. Further research needs to be conducted to cover large subjects, different area of nursing practice, and in a longitudinal observation involving additional sub variables.